2007
DOI: 10.1002/cncr.22730
|View full text |Cite
|
Sign up to set email alerts
|

New measure of health‐related quality of life for patients with oropharyngeal mucositis

Abstract: Scaffold‐guided tissue engineering based on synthetic and natural occurring polymers has gained much interest in recent years. In this article, the development of a polysaccharide‐based artificial extracellular matrix (AECM) is reported. Three‐dimensional, macroporous composite AECMs composed of chondroitin sulfate (ChS) and chitosan (Chito) were prepared by an interpolyelectrolyte complex/lyophilization method. The ChS–Chito composite AECMs were crosslinked with glutaraldehyde and calcium ions (Ca2+) and cocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 57 publications
1
31
0
9
Order By: Relevance
“…The OMQoL seems to be a clinically meaningful and scientifically robust HRQOL instrument, which can be completed in 8 min without assistance. Our factor analysis reported in previous literature supported the creation of symptom, diet, social function, and swallowing subscales [3], and these subscales demonstrated excellent construct validity in the current study.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The OMQoL seems to be a clinically meaningful and scientifically robust HRQOL instrument, which can be completed in 8 min without assistance. Our factor analysis reported in previous literature supported the creation of symptom, diet, social function, and swallowing subscales [3], and these subscales demonstrated excellent construct validity in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…Missing items are inevitable in any HRQOL measures. Nevertheless, previous validation results showed that the proportion of missing responses per item was low, with 5% of patients missing one item or more [3]. Various statistical approaches exist for dealing with the problem of missing data.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations